2010
DOI: 10.1126/science.1191883
|View full text |Cite|
|
Sign up to set email alerts
|

Relating Introspective Accuracy to Individual Differences in Brain Structure

Abstract: The ability to introspect about self-performance is key to human subjective experience, but the neuroanatomical basis of this ability is unknown. Such accurate introspection requires discriminating correct decisions from incorrect ones, a capacity that varies substantially across individuals. We dissociated variation in introspective ability from objective performance in a simple perceptual-decision task, allowing us to determine whether this interindividual variability was associated with a distinct neural ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

74
847
3
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 750 publications
(962 citation statements)
references
References 31 publications
74
847
3
2
Order By: Relevance
“…This includes Brodmann area 10 and dorsolateral prefrontal cortex, known to play an important role in linking objective performance to subjective beliefs (2,21). However, beyond these specific nodes, we also observed an increase in connectivity with an individual's type-II performance in a much broader network including ventrolateral PFC, bilateral inferior parietal lobules, angular gyrus, and bilateral precentral gyrus.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This includes Brodmann area 10 and dorsolateral prefrontal cortex, known to play an important role in linking objective performance to subjective beliefs (2,21). However, beyond these specific nodes, we also observed an increase in connectivity with an individual's type-II performance in a much broader network including ventrolateral PFC, bilateral inferior parietal lobules, angular gyrus, and bilateral precentral gyrus.…”
Section: Discussionmentioning
confidence: 53%
“…1A) (3). Type-II performance can be quantified by measuring the area under the receiver operating characteristic curve (A ROC ) (2,21). This nonparametric test estimates the degree of overlap between confidence distributions for correct and error trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, when examining the cerebral GMv correlates of EM in younger individuals of our sample, this set of regions included the bilateral angular gyrus, which is also a prominent structure within the DMN. The DMN mediates internal cognitive processes such as self‐referenced thoughts (Davey, Pujol, & Harrison, 2016) and introspective accuracy (Fleming, Weil, Nagy, Dolan, & Rees, 2010). Importantly, it has been shown that deactivation during encoding in the DMN regions, including posterior middle temporal cortices, predicted successful retrieval for the studied items (Chai, Ofen, Gabrieli, & Whitfield‐Gabrieli, 2014; Daselaar, Prince, & Cabeza, 2004; Kim, Daselaar, & Cabeza, 2010), that is, the ability to suppress their response during active memory tasks constitutes a prerequisite for efficient recall.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently increasing interest in meta-cognition with developments in its empirical study (Lau, 2008) and quantification (Galvin, Podd, Drga, & Whitmore, 2003). Although, as yet, we know little of relevant neural mechanisms, the prefrontal cortex is strongly implicated (Del Cul, Dehaene, Reyes, Bravo, & Slachevsky, 2009;Fleming, Weil, Nagy, Dolan, & Rees, 2010).…”
Section: Tpj Sts Mpfcmentioning
confidence: 99%